Development of physiological-based pharmacokinetic model 1 - model synthesis - Tan, Lisa Ying Xiu. (2009)
This project aims to improve on an existing physiological-based pharmacokinetic (PBPK) model on rats for drug candidate diazepam. The existing PBPK model has large discrepancy with the experimental results especially on the hepatic and gut tissue drug concentration. The existing PBPK discuss on intravenous administration only. This project aims to target and research on the hepatic and gut model to gap the discrepancy. This project also aims to discuss oral administration on the PBPK model. Significant and in-depth research had been made; the project includes implementation of a new and more complex methodology for the hepatic model and creation of a new gut model. Intravenous and oral administration is discussed. A Graphical User Interface is created for efficient and friendly access to the drug concentration graph results. RESULTS Based on a visual comparison, the in vivo concentration–time profiles were reasonably simulated with the new PBPK gut model on intravenous administration. The improvement of the gut model on intravenous administration serves as an important advancement for the existing PBPK model